2010
DOI: 10.1007/dcr.0b013e3181c52d1d
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Retroversion for Vaginoperineal Reconstruction Following Resection of Distal Rectal Tumors

Abstract: Uterine retroversion is a viable option for vaginal and perineal reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Post-exenterative vaginal reconstruction usually described in the literature refers to repair of pelvic fl oor and vaginal wall defects, rather than axis deviation (Berger et al 2010;Rettenmaier et al 2006;Castillo et al 2010). In a recent case report by Rettenmaier, successful reconstruction of a neovagina following pelvic exenteration was possible using an InteXen porcine mesh with the Apogee Ô and Perigee Ô devices (American Medical Systems, MN) (Rettenmaier et al 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Post-exenterative vaginal reconstruction usually described in the literature refers to repair of pelvic fl oor and vaginal wall defects, rather than axis deviation (Berger et al 2010;Rettenmaier et al 2006;Castillo et al 2010). In a recent case report by Rettenmaier, successful reconstruction of a neovagina following pelvic exenteration was possible using an InteXen porcine mesh with the Apogee Ô and Perigee Ô devices (American Medical Systems, MN) (Rettenmaier et al 2006).…”
Section: Discussionmentioning
confidence: 97%
“…The use of the intact uterus has been described in posterior vaginal wall reconstruction after proctectomy. 13 This is the first description of a uterine myoserosal flap reconstruction in posterior pelvic floor reconstruction.…”
Section: Discussionmentioning
confidence: 97%
“…Retroversion of the intact uterus has been described in filling the posterior defect created by proctectomy with excision of the posterior vaginal wall and was followed by satisfactory functional outcome and squamous epithelialization of the serosa. 13 Our exploration of this technique revealed that the intact uterus is not long enough to reach the skin edge posteriorly after the excision of anorectal cancer, especially when the perineum is excised. Anteversion of the intact uterus to fill the anteior pelvic floor after cystourethrectomy failed because the fundus of the uterus was too bulky to sit under the pubic arch and too short to reach the vestibule.…”
mentioning
confidence: 99%